Interactive effects of moderators on aggresion following violent video game play - Preman, Sharayah A (My University, 2015)
The present research examined how the ability to choose a heroic or deviant character role to play in a violent video game affects participants' subsequent aggression as a function of fantasy proneness. Participants were randomly assigned to play a violent game in one of four conditions (choice-heroic, choice-deviant, assigned-heroic, assigned-deviant). Participants in the assigned conditions played as either a heroic or deviant character. An induced compliance manipulation was used to create the perception of game choice by presenting half of the participants with the option to choose which role they wished to play. Immediately after violent game play, participants completed a measure of behavioral aggression (Taylor's Competitive Reaction Time Task) disguised as a multiplayer game. Results indicate that character role influenced aggression in both choice and assigned conditions. Furthermore, the ability to choose a role interacted with type of character role for those who displayed a higher degree of fantasy proneness. Those who were higher in fantasy proneness and had choice displayed a stronger character role effect on aggression than did those with no choice and lighter fantasy proneness. The character role effect for those lower in fantasy proneness was weakened and appeared relatively unaffected by whether they were able to choose the game.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Science-Psychology.
Keywords: Violence; Aggressiveness; Video games; Violence in video games